Analisis Penerapan dan Pengembangan Aplikasi SIMKASDA (Sistem Informasi Manajemen Kas Daerah) dalam Meningkatkan Efisiensi Keberhasilan dan Pelaporan Keuangan: Studi Kasus BPPKAD Kota Probolinggo - Ulfa Adiranti; Mohamad Djasuli (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the impact of implementing and developing the Regional Cash Management Information System (SIMKASDA) on efficiency, success, and financial reporting at the regional level. The research method used qualitative research, focusing on the use of SIMKASDA application in BPPKAD Probolinggo City. The results showed that the implementation of SIMKASDA significantly improved the efficiency of the regional cash management process. The system allows for more accurate monitoring of the DTH/RTH Reconciliation. This directly contributes to the success of local financial management by providing faster and more accurate information for stakeholders. Such improved success is also reflected in the transparency and accuracy of financial reporting. SIMKASDA provides a platform that enables faster and structured preparation of financial reports, minimizes human error, and strengthens accountability in the management of public funds. The discussion in this journal also identified some challenges faced during implementation, such as the need for intensive training and regular maintenance of the system. Research suggestions include increased training for users, regular system updates, and integration of the latest technology to ensure the continued success of SIMKASDA in the future. Thus, this study provides in-depth insight into the contribution of SIMKASDA in improving operational efficiency, financial management success, and financial reporting quality at the local level.